Diversity management in Spain : new dimensions, new challenges - Zapata-Barrero, Ricard (New York : Manchester University Press ; Distributed in the U.S. exclusively by Palgrave Macmillan, 2013)
"This book argues that Spain represents a context of 'multiple diversity', where two frameworks interact: an old, unresolved one, arising from democratic transition, and a new one due to immigration. This explains the Spanish practical approach, where the recent past plays the role of an iron cage, limiting institutional innovation and change. The author proposes a heuristic model, to better understand the 'Spanish laboratory of diversities'. In order to go through these steps, the author analyses three case studies, coming from the political/social agenda: education, workplace, and political rights."--Page 4 of cover.